PROTECTIVE EFFECT OF Ailanthus excelsa ROXB IN MYOCARDIAL INFARCTION POST MESENCHYMAL STEM CELL TRANSPLANTATION: STUDY IN CHRONIC ISCHEMIC RAT MODEL - Gong, Xia (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Thia study evaluates the effects of Ailanthus excelsa Roxb methanolic extract (AER-ME) in rats induced with Myocardial Infarction (MI) followed by transplantation of MSCs. Material and Methods: Rats were induced with MI by ligation technique of left coronary artery. The sham-operated the control and AER-ME treated group of rats received transplantation of PKH-26 and marked MSCs followed by normal saline and AER-ME treatment (200mg/kg/day of AER-ME extract) respectively for 30 days. Parameters such as cardiac function, inflammation, oxidative stress, apoptosis and differentiation of MSCs (angiogenesis) were evaluated. Histological studies of infracted myocardium reveled antiinflammatory activity of AER-ME treatment. Result and Discussion: Oxidative stress parameters revealed decrease in levels of malondialdehyde (MDA) and increase in superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSHpx) activity significantly indicating antioxidant activity of the extract. There was a reduction in cell death rate of treated rats due to the decrease in apoptotic index with prolongation of MI when compared to both control and sham-operated groups. The expression of Fas protein was parallel to apoptotic index. The vascular density increased significantly in extract treated group. The treatment showed improved cardiac activity with decreased left ventricular end diastolic (LVEDP) and arterial pressure while the left ventricular end systolic pressure (LVEP) and dp/dtmax increased significantly when compared to both control and sham-operated groups respectively showing the protective effect of the extract as necessitated by the transplantation of MSCs. The study marked the protective outcomes of AER-ME treatment for MSCs in microenvironment of infracted myocardium by improving their viability and increasing differentiation into cardiomyocytes.